The Meaning of Kutiba in the Ramadan Fasting Verse: Semantic Approach - Ahmad Ismail (Alfaz (Arabic Literatures for Academic Zealots), 2022)
The word kutiba in the Qur'an which means obligation is used 4 times. One of them is the obligation to carry out fasting. The purpose of this study is to describe the meaning of the word kutiba contained in QS 2: 183-185. This type of research is qualitative research using the Descriptive method of analysis. The instruments used in this research are the researchers themselves and are assisted by documentation studies. The source of data in this study is QS 2, 183-185. Data analysis is carried out in the following way. First, syntagmatic analysis and paradigmatic analysis. Second, interpret the results of syntagmatic and paradigmatic analysis. Third, find weltanschaung. The results showed the following. (1) In Q.S 2:183, the word kutiba means obligation (furidha). (2) The word kutiba which means obligation has a characteristic, namely an obligation or duty that is not liked and the obligation is delivered in a loud tone. (3) QS 2:184 and 185 were revealed not to inform that believers may not fast if they are sick or travel long distances. However, the verse was revealed as an affirmation of the importance of the obligation to fast in Ramadan, so the sentence is repeated twice in succession. (4) Wa an taṣụmụ khairul lakum ing kuntum ta'lamụn (2:184) means and fasting is better for you if you know. So it can be concluded that the obligation to fast in Ramadan is an obligation that must be done by believers under any circumstances. Fasting in Ramadan is better if you understand it.